Smart Medicine Dispenser / Ahmad Irfan Mohd Saiffie … [et al.] - Mohd Saiffie, Ahmad Irfan; Anwar, Atqan; Kamaruzzaman, Umar Farooq; Wan Mansor, Wan Nur Melissa Huda; Mohamad Har, Harmi Azwa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
In today's medical landscape, the reliance on pills and tablets is widespread, crucial for maintaining well-being. This paper introduces an smart medication dispenser (SMD) designed for elderly or senior patients managing their medication independently. By handling medication instructions and dosing accurately, it enhances adherence to schedules and reduces errors in management. This electronic pill dispenser features a PIC microcontroller with a keyboard and LCD, enabling manual scheduling, dispensing, alarms, and SMS alerts for missed doses. Another dispenser uses infrared sensors and an Arduino microcontroller with a smartphone notification system for timely intake. A third, Arduino-based dispenser prevents overdosing by dispensing one pill at a time, sending SMS alerts, and integrating with an Android app for caretaker control of schedules.